Sistema fotovoltaico residencial conectado à rede em Santarém: estudo de viabilidade técnica e financeira - OLIVEIRA, Gisllane Santos de (Universidade Federal do Oeste do Pará, 2024)
In areas with access to the distribution grid, Grid-Connected Photovoltaic Systems (SFCRs) emerge as an economic and environmental option for generating electricity. Distributed Generation connected to the grid was regularized in 2012 through the National Electric Energy Agency’s (ANEEL) Normative Resolution N° 482 of, which allows the Brazilian consumer to generate electricity from renewable micro and mini-systems and provide the surplus to the distribution grid. In this scenario, this study aims to evaluate the financial viability of the deployment of a SFCR in a middle-class residence located in the city of Santarém, Pará, with the average consumption of 250 kWh / month, within the regulatory framework provided by the Brazilian and local markets. For technical viability analysis there was a literature review of available technology, the development of the electrical project of the proposed system and its submission to the local utility for approval. For the financial analysis a Turnkey design was quoted and evaluated in terms of the Return Of Investiment (ROI) and Internal Return Rate (IRR) over the expected service life of the system, with the investment capital from the owner’s savings and from bank financing. Due to economic factors in the country, the Brazilian compensation model, the absence of a local specialist company, the proposed SFCR proved, to date, to be economically unfeasible in the region, without discarding the feasibility of higher consumption profiles. In addition, the adoption of SFCRs in Brazil is incipient, requiring changes in some sectors so that it becomes a competitive generation system on the market.